Feasibility and efficacy of left bundle branch area pacing in patients indicated for cardiac resynchronization therapy. (28th December 2020) - Li, Yuqiu; Yan, Lirong; Dai, Yan; Zhou, Yu'an; Sun, Qi; Chen, Ruohan; Lin, Jinxuan; Jin, Yuanhao; Chen, Feng; Guo, Xiaogang; Chen, Keping; Zhang, Shu
Abstract: Aims: The present study was to evaluate the feasibility and clinical outcomes of left bundle branch area pacing (LBBAP) in cardiac resynchronization therapy (CRT)-indicated patients. Methods and results: LBBAP was performed via transventricular septal approach in 25 patients as a rescue strategy in 5 patients with failed left ventricular (LV) lead placement and as a primary strategy in the remaining 20 patients. Pacing parameters, procedural characteristics, electrocardiographic, and echocardiographic data were assessed at implantation and follow-up. Of 25 enrolled CRT-indicated patients, 14 had left bundle branch block (LBBB, 56.0%), 3 right bundle branch block (RBBB, 12.0%), 4 intraventricular conduction delay (IVCD, 16.0%), and 4 ventricular pacing dependence (16.0%). The QRS duration (QRSd) was significantly shortened by LBBAP (intrinsic 163.6 ± 29.4 ms vs. LBBAP 123.0 ± 10.8 ms, P < 0.001). During the mean follow-up of 9.1 months, New York Heart Association functional class was improved to 1.4 ± 0.6 from baseline 2.6 ± 0.6 ( P < 0.001), left ventricular ejection fraction (LVEF) increased to 46.9 ± 10.2% from baseline 35.2 ± 7.0% ( P < 0.001), and LV end-diastolic dimensions (LVEDD) decreased to 56.8 ± 9.7 mm from baseline 64.1 ± 9.9 mm ( P < 0.001). There was a significant improvement (34.1 ± 7.4% vs. 50.0 ± 12.2%, P < 0.001) in LVEF in patients with LBBB. Conclusion: The present study demonstrates the clinical feasibility of LBBAP in CRT-indicated patients. Left bundle branch area pacing generated narrow QRSd and led to reversal remodelling of LV with improvement in cardiac function. LBBAP may be an alternative to CRT in patients with failure of LV lead placement and a first-line option in selected patients such as those with LBBB and heart failure.